Politics, Poetics and Propriety: Reviewing Amelia Opie - King, Shelley (Romanticism on the Net, 2003)
AbstractTracing out the stages of the reception history of Amelia Opie’s poems, this essay shows that changes in assumptions about sensibility and women’s poetics whereby they came to be gendered “feminine and weak” reduced the political power of Opie’s poetry. Not only Opie’s contemporaneous reviewers but also Opie herself, following their lead in her later publications, enacted a shift in focus from the politics of class to the poetics of gender. At first, the radicalism of some of Opie’s poems that focus on class combined with her appropriately gendered use of a poetics of sentiment rendered conservative reviews ambivalent in their evaluations of her poetry: they approved of the sentimentality but sensed political danger. As Opie accommodated her reviewers’ criticisms, her poetry increasingly conformed to a feminine poetics that obscured the anti-classist and anti-racist radicalism constitutive of her earlier poetics. The political is definitively laid to rest by later generations of critics who see Opie’s work as reflecting rather than analyzing the feelings of her time and thus as merely of nostalgic interest.